2009
DOI: 10.1002/mds.22558
|View full text |Cite
|
Sign up to set email alerts
|

Is the pathology of corticobasal syndrome predictable in life?

Abstract: Corticobasal syndrome (CBS) has been associated with a heterogeneous spectrum of pathologies with an increasing number of reports of Alzheimer's type pathology. There is, however, no means of predicting pathology of CBS in vivo at present. We compared the clinical features of patients presenting with CBS who have either pathologic changes of classic corticobasal degeneration (CBD) or Alzheimer's disease (AD) at post-mortem to identify predictors of the specific pathological processes in life. Twelve patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
152
1
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(174 citation statements)
references
References 41 publications
9
152
1
12
Order By: Relevance
“…22 The CBS-AD group scored significantly lower on the orientation-memory subtest of the Mattis DRS-2 in primary and secondary analyses. Of note, patients with CBS-AD also perform worse on the orientationmemory subcomponent of the Addenbrooke's Cognitive Examination, 9 and a recent review of 42 CBS cases identified memory impairment as being associated with CBS-AD 11 (although the nature of this impairment was not precisely defined). It remains difficult to determine which aspect of memory may be impaired because of the inclusion of orientation in this scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The CBS-AD group scored significantly lower on the orientation-memory subtest of the Mattis DRS-2 in primary and secondary analyses. Of note, patients with CBS-AD also perform worse on the orientationmemory subcomponent of the Addenbrooke's Cognitive Examination, 9 and a recent review of 42 CBS cases identified memory impairment as being associated with CBS-AD 11 (although the nature of this impairment was not precisely defined). It remains difficult to determine which aspect of memory may be impaired because of the inclusion of orientation in this scale.…”
Section: Resultsmentioning
confidence: 99%
“…Frequently, patients with CBS are found, postmortem, to have pathology of Alzheimer disease (CBS-AD), progressive supranuclear palsy (CBS-PSP), or other non-CBD pathologies. [3][4][5][6][7][8][9][10] Of the various pathologic substrates of CBS, AD is common, accounting for more than 20% of cases. 3,5,9,10 Antemortem diagnosis of CBS-AD is important, because patients may benefit from cholinesterase inhibitors or future AD-targeted treatments.…”
mentioning
confidence: 99%
“…5,8,9 For example, cortical Neurology.org/cp sensory loss and myoclonus, classically considered key features of CBD, have in fact been shown to be associated with either CBD or Alzheimer disease (AD) pathology. 7,10 While the motor syndrome of CBS is distinct from other neurodegenerative parkinsonian syndromes, there are few specific motor features that reliably predict underlying pathology.…”
Section: Clinical Features Of Cbsmentioning
confidence: 99%
“…One study suggested that episodic memory complaints may predict AD pathology in patients with CBS, and evidence for frontal lobe dysfunction (such as nonfluent language deficits and utilization behavior) may predict CBD. 10 However, others have not demonstrated distinct cognitive profiles in CBS cases with underlying AD vs CBD pathology. Alzheimer disease 16,17 Pick disease 12,17 Progressive supranuclear palsy 17 Dementia with Lewy bodies (Gross et al, personal communication, 2013)…”
Section: Clinical Features Of Cbsmentioning
confidence: 99%
“…Although initially described as a predominantly motor syndrome, an increasing number of cases in whom cognitive involvement predominates have been reported [1,2,3,4,5,6,7]. As a result, CBS is now regarded as a complex disorder which affects motor and cognitive function although the relative importance of these two major features remains controversial.…”
Section: Introductionmentioning
confidence: 99%